Healthy cats tolerate long-term daily feeding of Cannabidiol - Coltherd, Jennifer C.; Bednall, Robyn; Bakke, Anne Marie; Ellerby, Zack; Newman, Christopher; Watson, Phillip; Logan, Darren W.; Holcombe, Lucy J. (Frontiers in Veterinary Science, 2024)
Cannabidiol (CBD)-containing products are widely commercially available for companion animals, mirroring popularity in human use. Although data on the safety and efficacy of long-term oral supplementation are increasing in dogs, evidence remains lacking in cats. The purpose of these studies was to address gaps in the knowledge around the long-term suitability and tolerance of a tetrahydrocannabinol (THC)-free CBD distillate in clinically healthy cats. The studies were randomized, blinded, and placebo-controlled. The first study supplemented cats with either a placebo oil (n = 10) or with 4 mg/kg body weight (BW) CBD in placebo oil (n = 9) daily, with a meal, for 4 weeks. The concentration of CBD in plasma was measured over 4 h at d0 (first dose) and again at d14 (after 2 weeks of daily dosing). The second study supplemented cats daily with either placebo oil (n = 10) or 4 mg/kg BW CBD in placebo oil (n = 10) for a period of 26 weeks. A comprehensive suite of physiological health measures was performed throughout the study at baseline (week 0) and after 4, 10, 18, and 26 weeks of feeding, followed by a 4-week washout sample (week 30). Postprandial plasma CBD time course data, at both d0 and d14, showed a peak plasma CBD concentration at 2 h after the dose. This peak was 251 (95% CI: 108.7, 393.4) and 431 (95% CI, 288.7, 573.4) ng/mL CBD at d0 and d14, respectively, and the area under the curve concentration was higher by 91.5 (95% CI, 33.1, 149.9) ng-h/mL after 2 weeks of supplementation (p = 0.002). While in the first study the CBD group displayed increased alanine aminotransferase (ALT; 68.7 (95% CI, 43.23, 109.2) U/L) at week 4 compared to the placebo control group [1.44-fold increase (95% CI, 0.813, 2.54)], statistical equivalence (at 2-fold limits) was found for ALT across the duration of the second, long-term study. All other biochemistry and hematology data showed no clinically significant differences between supplement groups. Data presented here suggest that a THC-free, CBD distillate fed at a dose of 4 mg/kg BW was absorbed into plasma and well tolerated by healthy cats when supplemented over a period of 26 weeks.